Psychology of text comprehension: Problems and possibilities of empirical investigations - Rimkutė, E. (Psichologija, 1993)
The paper is concerned with present of theoretical and methodological problems of text comprehension in psychology. The investigations of the language in psycholinguistics and cognitive psychology which influenced the formation of the present paradigms of text comprehension are discussed. Pilot study on the application of the phenomenological method in the investigation of text comprehension is described and empirical data representing individual differences in the comprehension of miraculous tale are discussed.
Keywords: text comprehension; psycholinguistics